NEW EFFECTIVE METHODS OF TOMATO CULTIVATION AND PROCESSING IN THE FOОTHILL AREA OF THE REPUBLIC OF DAGESTAN - A. M. Gadgieva; M. S. Muradov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The peculiarities of tomato cultivation and processing in conditions of plain area of Dagestan have been considered in the article. The layout of integrated tomato processing and the hardware layout of lines of tomato processind hae been described.The new effective method of tomato-juice production is developed.